DEVELOPMENT OF MATHEMATICAL COMPETENCE OF FUTURE PRIMARY SCHOOL TEACHERS (ON THE EXAMPLE OF NATURAL RESOURCES) - Ismoilov Bobur Toxirovich (Bright Mind Publishing, 2025)
The article investigates the issue of envisioning mathematical science of utilizing water, which is the second need of man, specifically, to decide the arrangement of an (a:b) division, to locate the number average mean, and to clarify the idea of fractions are shown through a “water counter”.
Keywords: Water counter, one cubic unit of water, barrier, water level, law of contiguous vessels, division operation, arithmetic mean value, fractional concept.